Metode Pemaparan Qirâ’at dalam Tafsir Fath Al-Qadir oleh Imam Al-Syaukâni - Hidayatullah Ismail; Diki Agrastiadi; Mochammad Novendri S; Dasman Yahya Ma'ali (Jurnal An-Nur, 2022)
This article is entitled the method of explaining Qirâ'at in the book of commentary on Fath al-Qadir by Imam al-Syaukâni. In interpreting the Qur'an, al-Syaukâni also very often uses the Qira'at approach in explaining the meaning of the sentences of the Qur'an. This article examines how al-Syaukâni applies methods to the differences in Qirâ'at in his interpretation, and how al-Syaukâni's method resolves differences in Qirâ'at in his interpretation. Using a descriptive-analytical approach, this study examines the basic concepts of the rules of interpretation of the differences in Qirâ'at, looks for the roots of the character's thoughts, explains the advantages and disadvantages of the method including its implications. From the results of the discussion, it can be concluded that in the explanation of Qirâ'at, al-Syaukâni mentions which opinion is the strongest. Almost every verse that is interpreted is always made comparisons, this can be seen from the nazhair Qur'an (the similarity of meaning in other verses), as well as comparing the readings of the Qira'at of the Qurra'. Al-Syaukâni examines the strongest opinion from various interpretations by determining and explaining its meaning in the form of interpretations of al-Riwayah and al-Dirayah. Al-Syaukâni also uses three methods of approach, namely majhul, ma'lum, and istisyhad (proof with Arabic poems).